Occupational segregation and the gender wage gap in Brazil: an empirical analysis - Madalozzo, Regina (2010)
Several countries experienced an increase in female labor participation during the twentieth century. Even so, few can be proud of the conditions female workers faced. This paper analyzes the occupational distribution by gender from 1978 to in 2007 in Brazil. It shows that women have penetrated traditionally male occupations to a certain extent, but that traditionally female occupations have maintained their gender composition over the past 30 years. We also provide a regression analysis with an Oaxaca decomposition that shows that the gender wage gap is lower than in 1978, but that it has remained constant over the last decade.